Analisis Dan Perancangan Sistem Informasi Geografis Pemetaan Bencana Alam Di Provinsi Jambi - Eltha, Rico Janpria; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2020)
Badan Penanggulangan Bencana Daerah (BPBD) Jambi regarding natural disasters, BPBDs not have asystem to perform disaster data refineries. All data held regarding natural disaster event data is stillprocessed using Microsoft Excel. As well as the delivery of information relating to natural disasters is notmaximized, to address this issue pelu built an information system data processing of natural disasters thatwill make it easier to manage data BPBDs disasters and provide information directly to the public. Ofthese problems the author tries to analyze and design a Geographic Information System Mapping NaturalDisasters In Jambi Province using UML system modeling and produce a design of the display in the formof a prototype. With the stem Mapping Geographic Information Disaster In Jambi Province Disasterfacilitate Badan Penanggulangan Bencana Daerah (BPBD) in managing the data of natural disasters andeasier for people to get information.